PENGARUH INTENSITAS MENONTON TELEVISI TERHADAP MINAT BELAJAR SISWA MIS AL KHAIRAT DELI TUA T.A 2021/2022 - Siti Zahara H. Harahap; Rinci Simbolon; Anggi Perbina Br Peranginangin (JURNAL CURERE, 2022)
This study aims to determine the effect of television viewing intensity on student interest in MIS Al Khairat Deli Tua. The research will be carried out in July 2021 in the Even Semester of the 2021/2022 Academic Year at MIS AL Khairat. The population in this study were all students of class V MIS Al Khairat, totaling 50 students. The sample in this study was class VB which amounted to 24 students. Based on research data from the results of questionnaires on the intensity of watching television, the highest score was 76 and the lowest score was 31. The calculation results obtained an average score (X) = 52.55 with standard deviation (s) = 7.193. The indicator of the quality of depth or duration of watching television with a score of 2,363 (40.49%) and for the lowest score is the third indicator, namely the power of concentration or attention to watch television 1,526 (26.15%). Furthermore, each respondent's answer to the indicator of the intensity of watching television is categorized in the following table based on the Likert scale. The indicator that has the highest score is the third, namely the activeness of children in learning with a score of 1270 (20.11%) and the lowest score is the sixth indicator, namely getting a sense of security with a score of 676 (10.70%). The results showed that there was an effect of the intensity of watching television on students' interest in learning. This can be interpreted that the intensity of watching television can have a positive influence on students' interest in learning